2013
DOI: 10.1177/1352458513475833
|View full text |Cite
|
Sign up to set email alerts
|

High risk of cardiovascular diseases after diagnosis of multiple sclerosis

Abstract: We recommend careful surveillance and preventive CVDs measures among MS patients, particularly among the women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(167 citation statements)
references
References 36 publications
12
145
0
10
Order By: Relevance
“…We and others have shown a higher than expected incidence of cardiac disease in MS. 8,9 As hypothesized, we found that infection was a more common reason for ICU admission in the MS population than in the general population. Immunosuppressive therapy was associated with admission for infection, but adjusting for immunosuppressive therapies did not eliminate the association with admission for infection.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…We and others have shown a higher than expected incidence of cardiac disease in MS. 8,9 As hypothesized, we found that infection was a more common reason for ICU admission in the MS population than in the general population. Immunosuppressive therapy was associated with admission for infection, but adjusting for immunosuppressive therapies did not eliminate the association with admission for infection.…”
Section: Resultssupporting
confidence: 53%
“…[1][2][3][4] While chronic diseases are established risk factors for ICU admission and mortality, 5,6 little is known about the influence of immune-mediated diseases such as multiple sclerosis (MS) on ICU admissions. MS is associated with increased risks of infection 7 and ischemic heart disease, 8,9 which could increase the risk of ICU admission. However, hospitalized elderly patients with MS have been reported to be less likely to use intensive or coronary care services than other patients.…”
mentioning
confidence: 99%
“…Sternberg and colleagues also reported that there was no significant difference in the use of antihypertensive drugs between MS and non-MS patients. Lower prevalence of hypertension was also reported by some studies [19,54]. For example, in study of 8281 MS patients by Jadidi and his colleagues, the frequency of hypertension was lower in MS patients compared to the matched controls (0.42% versus 0.68%) [54].…”
Section: Prevalence Of Hypertension In People With Ms and Comparison mentioning
confidence: 54%
“…Furthermore, while we have demonstrated associations between pain, depression, and CVD in individuals with SCI, the implications of our study have much broader clinical implications. Indeed, other neurological conditions, accompanied by neuropathic pain and depression in the early stages of disease, and high incidence of CVD at later time points (e.g., multiple sclerosis), may be subject to similar increased risk [28]. …”
Section: Discussionmentioning
confidence: 99%